Exploring the Challenges of Goods and Services Tax on Batik Manufacturers - Yaacob, Zalilawati; Abd Hamid, Nadiah; Fara Shahirah Kamal, nor; Ghazali, Noorlaila; Shamsuddin, Roszil (International Journal of Engineering and Technology, 2018)
The implementation of Goods and Services Tax (GST) in Malaysia has received criticism from various parties such as businesses, policy makers, professionals, business associations and individuals. Despite the rejections from these parties, the government proceeded to implement GST on 1 April 2015. Subsequently, this led to difficulties encountered by businesses, particularly the manufacturing industry in adjusting the production cost, setting prices of products, and comply with the new indirect tax structure. Hence, this study aims to explore the challenges of GST on SME batik manufacturers pertaining to business performance and compliance. A semi structured interviews were conducted on the top management and owners of SME batik manufacturer in two states of Malaysian Peninsular, namely Kelantan and Terengganu. The respondents reported that, during the era of GST, sales of their batik products decreased tremendously. In addition, they described the GST system as a complex system that affects compliance. This study solicits governmentâ€™s attention on the impact of GST on Malaysian batik manufacturers. The findings suggest that it is essential for government to devise plans in reducing the financial burden of batik manufacturers and to simplify the GST mechanism in encouraging a high level of GST compliance.Â